Scenario Planning for Indonesian FDA In the Enforcement of GMP Guideline for Traditional Medicine 2021 Edition - Rahma Yulianti; Bambang Purwoko Kusumo Bintoro (AIBPM Publisher, 2021)
The continuity of a country’s Drug NRA as a PIC/S member is determined by GMP Guideline that recognized in member country should equivalent with PIC/S GMP Guideline. GMP Guideline for TM / CPOTB currently enforced in Indonesia and harmonized with PIC/S is the 2021 edition. Indonesian FDA identified that there are significant gaps between GMP Guideline for TM 2021 edition compare to previous edition, as well as varied implementation capability in IOT and IEBA causing future uncertainties for Indonesian FDA in enforcing the guideline. To develop the strategy for Indonesian FDA to face future uncertainties, a scenario planning approach is utilized. The key focal issue of this research is how the Indonesian FDA enforced the implementation of the 2021 edition of the GMP Guidelines for TM to IOT and IEBA in the next 5 years. There are 13 driving forces that have been identified and 2 of them, which are free trade and government policy, identified as critical uncertainties. Scenarios are generated in 2x2 matrix that developed from critical uncertainties. Implications and options are defined for each scenario and challenge the Indonesian FDA to perform actions in order to plan strategies to face uncertainties in the future.